Analisis Tinggi Tanggul Sebagai Bangunan Pengendali Banjir Menggunakan Metode HEC-RAS - Fatharani, Aghnia; Sujatmoko, Bambang; Rinaldi, Rinaldi (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2018)
The area located on the banks of the Sail River, especially the downstream part of the river is an area that hasthe potential to flood and puddle when the rainfall is high in the upper reaches and the influence of the high tideof the Siak river. Floods that occurred on the banks of the Sail River inundated several infrastructures such asroads and residential areas. Based on Antara (2017), in Bambu Kuning street, the village of Rajosari was hit bya puddle of Sail river as high as about 30-60 cm, while around the residential area the height of the water was20 cm. The stages of the research are analyzing the frequency of rainfall data first, then calculating the planneddischarge with Nakayasu HSS, then hydraulic modeling using the HEC-RAS Program, after the flood waterlevel is obtained, the embankment planning is carried out. Based on the results of the analysis of the Sail Riverflood height, it was found that the flood face elevation in the upstream river, cross section 61 (SC 61) is 7.91 mor 1.57 m from the left bank of the river and 1.51 m from the right bank of the river and elevation flood face inthe downstream, cross section 0 (SC 0) is 2.67 m or -2.85 m from the left bank and -1.77 m from the right bank(non-flood conditions). After normalization, the height of the embankment plan is an elevation of 5.5 m at sta 0+ 050, elevation of 7 m sta 0 + 150-sta 2 + 150 (2000 m), elevation of 7.5 m sta 2 + 200-sta 3 + 050 (850 m)thus the water level elevation in the Sail river has decreased ± 1 m.Keywords: flood, embankment, HEC – RAS